Analysis of Kevin Lynch's Theory of City Image (Case Study of The Tanah Abang Area in Jakarta) - Yusup Salam; Renny Nurhasana (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
In the midst of development, revitalization, and the influence of globalization, of course, more or less will affect identity in an area, building an image in an area is important to strengthen identity and can be used as a reference in determining the orientation value of appropriate spatial planning. In this study, the researcher used a case study approach to explore data as a basis for giving deep meaning to the selected cases according to the research topic, namely Kevin Lynch's Theory Analysis of City Image in the Tanah Abang area. Researchers have collected all the data findings and described them, related to the five main image formers of the Tanah Abang area which consist of Paths, Edges, Nodest, District, and Landmarks. At least the researcher can describe the image of the Tanah Abang area as having five main access roads as a link between the outside areas, finding six findings as signs of area boundaries in the form of river flows and mid-road barriers, there are seven districts divided based on their function, there are four main meeting points of intersection, and four landmarks as symbols that can be perceived about the Tanah Abang area.